G394(P) Infection and wheeze in the first 6 months of life – an interim analysis of the go-child birth cohort. (27th April 2015) - Basu, K; Fidler, K; Abd, AJ; Inglis, SK; Henry, M; Memon, A; Rabe, H; Seddon, P; Tavendale, R; Palmer, CNA; Mukhopadhyay, S
Abstract : Aims: The aim of the GO-CHILD birth cohort study is to understand the natural history of common childhood diseases like asthma, allergies and infections and to investigate the role of gene-environmental interactions in childhood diseases that present very early in life. We wish to understand how these associations during 0–2 years relate to our previous observations on older children. We report our interim observations regarding disease phenotype at 6 months of age. Methods: GO-CHILD is a multicentre prospective birth cohort study. 2315 infants were recruited from antenatal clinics across the UK and followed up at the ages of 3, 6, 9, 12 and 24 months through postal questionnaires. The 6-month questionnaire explores infection and atopy related events in the first 6 months of life. Results: 938 participants returned the completed 6-month questionnaire. 106 (11%) infants had been admitted to the special care baby unit, of whom 41% had confirmed or suspected infections and 40% reported breathing problems. 130 (13.8%) children reported wheeze in the first 6 months of life. Among them, 124 (95%) reported this as viral-induced, 25 (19%) had more than 3 attacks of wheeze, 31 (24%) were prescribed inhalers and 20 (15.4%) reported having disturbed sleep once or more nights per week. 156 (17%) infants required hospital admission in their first 6 months of life, with 36/938 (4%) requiring more than one admission. Of the children experiencing any hospital admission, 17% received oral antibiotics, while 24% received intravenous antibiotics. 646 (69%) infants had visited the GP at least once, of whom 93 (14%) received antibiotics for probable infections. 95% of the participants returning the 6-month questionnaire were fully immunised. Conclusion: Despite the possible bias of those returning questionnaires, our interim results indicate a high prevalence of infection and wheeze during the first 6 months of life in UK infants. Approximately 14% had experienced wheeze, 14% received oral antibiotics from the GP and 17% reported being admitted to hospital. We wish to further explore the association of genetic variations and their interactions in the context of childhood infections and atopy. The study was funded by the children's charity SPARKS.